Imprensa e resistência católica durante os Anos de Chumbo da Ditadura Militar no Brasil - Silva, Newton Leonardo (2019)
In order to understand the relationship between the Catholic Church and the Brazilian Military Government at the stage which became known as the “Lead Years” and how this game of interests between the two institutions with the most political power in the national scenery was built, a study of the published materials on a media outlet from the Metropolitan Curia of São Paulo, known as O São Paulo, is conducted. The period studied goes from November of 1970, when D. Paulo Evaristo Arns, then responsible for Pastoral Carcerária, was named by Pope Paul VI as the fifth Archbishop of São Paulo City, succeeding the conservative D. Angelo Rossi; and the month of March of 1974, when the most opressive period of the dictatorship, commanded by General Emilio Garrastazú Médice, came to an end. According to the study, it has been found that despite censorship, the newspaper made an extremely opinionated coverage. Such fact translates the archbishop’s spirit in relation to the city of São Paulo, D. Paulo Evaristo Arns, who opted to confront the military respectfully and diplomatically, and in national territory